Optimering av reducerad bearbetning - Wiklund, Nils (2014)
Optimization of soil tillage and crop rotation is important in many aspects, but particularly in maximizing profit margins. Since the economic outcome is usually decisive, it can be interesting to study different combinations of soil tillage systems and crop rotations in order to identify the maximum economic outcome. How a crop functions in a particular tillage system determines whether it is profitable to grow that crop. Different tillage systems affect the soil and its processes in different ways. Reduced tillage often works best on weak-structured heavy clays and on silty clays. However, the positive effects arising from reduced tillage can take a few years to develop, so it is necessary to study such systems over longer periods.